Delayed Presentation of Suture Erosion following Burch Colposuspension - Robert Shapiro; Ali Hajiran; Stanley Zaslau (Case Reports in Obstetrics and Gynecology)
Background. Synthetic mid-urethral mesh slings are the most common primary surgical treatment for stress urinary incontinence (SUI) and have been designated as the standard of care by the American Urogynecologic Society. In recent years, synthetic mesh has come under increased scrutiny by the Federal Drug Administration (FDA) due to concerns over patient safety. This has led to more surgeons and patients preferring Burch colposuspension to treat SUI. Case. We discuss two cases of suture erosion into the urethra and bladder. They presented with irritative voiding symptoms and recurrent urinary tract infections. Both were discovered years after a Burch colposuspension. Conclusion. As reported in the literature as early as 1999, erosion is a complication associated with many types of incontinence surgery and not unique to mesh based sling operations. Burch colposuspension should not be favored solely to avoid erosion and patients should be counseled accordingly. Teaching Point. Cystourethroscopy performed intraoperatively or postoperatively is essential for early diagnosis and treatment of complications related to incontinence surgery.